Gendered time-budgeting, affective wellbeing, and its implication for cognitive health among older adults in India - Dipti Govil; Harihar Sahoo; Srei Chanda; K. S. James (Discover Public Health)
Abstract Studying time usage can comprehensively reveal the pathway for affective wellbeing and cognitive outcomes among older adults. Using unit-level data on 4951 older adults from the World Health Organization’s Study on Global AGEing and Adult Health (WHO-SAGE-1), the paper aims to understand the plausible effect of time-weighted experienced wellbeing on gendered cognitive aging in India. Descriptive statistics and ordinary least squares regression were used to measure the net effects of emotions and experienced utility on cognitive outcomes. Older adults were found to spend the most time at work each day, with males spending 172 min and females spending 141 min. Self-care and household chores/caregiving were next in order. Cognition was positively associated with leisure activity-specific net affect among males and leisure and self-care activity-specific net affect among females. The time-specific effects of leisure and self-care activities were negatively associated with cognition. Strong gender segregation was observed in the type of activities performed and the time allocated to them. The study highlights that older adults with better net affect or satisfaction have better cognitive outcomes. The results suggest a focus on rejuvenating activities while designing programs and policies targeted at older people to promote active and healthy aging.